1994
DOI: 10.3109/02656739409012372
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthermic potentiation of cisplatin toxicity in a human small cell lung carcinoma cell line and a cisplatin resistant subline

Abstract: A human small cell lung carcinoma cell line (GLC4) and its subline with in vitro acquired cisplatin (cDDP) resistance (GLC4-cDDP) were used to study the applicability of hyperthermia to interfere with acquired cDDP resistance. GLC4 and GLC4-cDDP did not differ in heat sensitivity (clonogenic ability). Both cell lines could be sensitized to cisplatin to a considerable extent, both at 42 and 43 degrees C. For 42 degrees C hyperthermia treatments up to 90 min no differences in TER between the cell lines were obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0
2

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 8 publications
1
22
0
2
Order By: Relevance
“…We have shown that these pleiotropic effects of heat are also effective in enhancing cDDP accumulation, adduct formation and/or adduct removal in cDDP-resistant cells. This indicates why the multifactorial aspects of hyperthermia have been found to be so suitable for the (partial) reversal of cDDP resistance in a variety of cell lines with different mechanisms of resistance (Wallner et al, 1986;Herman et al, 1988;Mansouri et al, 1989;Konings et al, 1993;Hettinga et al, 1994; this study). Therefore, our data provide a scientific basis for supporting the use of combined heat and cDDP chemotherapy in cDDP-resistant tumours, and therefore this combined modality deserves further attention in the clinic.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…We have shown that these pleiotropic effects of heat are also effective in enhancing cDDP accumulation, adduct formation and/or adduct removal in cDDP-resistant cells. This indicates why the multifactorial aspects of hyperthermia have been found to be so suitable for the (partial) reversal of cDDP resistance in a variety of cell lines with different mechanisms of resistance (Wallner et al, 1986;Herman et al, 1988;Mansouri et al, 1989;Konings et al, 1993;Hettinga et al, 1994; this study). Therefore, our data provide a scientific basis for supporting the use of combined heat and cDDP chemotherapy in cDDP-resistant tumours, and therefore this combined modality deserves further attention in the clinic.…”
Section: Discussionmentioning
confidence: 71%
“…In addition, relatively high heat doses (above 42°C) can (partly) reverse in vitro acquired cDDP resistance (Wallner et al, 1986;Herman et al, 1988;Mansouri et al, 1989;Konings et al, 1993;Hettinga et al, 1994). Resistance to cDDP is a major problem in the clinic and limits the success of this drug.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A hyperthermic potentiation of intracellular drug accumulation could be demonstrated for cisplatin only in cisplatin-resistant but not in-sensitive cell lines. Other mechanisms of hyperthermic potentiation such as increased DNA adduct formation and DNA damage could be demonstrated to the same extent in sensitive and resistant cells [43]. Doxorubicin is the only anthracycline which has been extensively studied in combination with HT.…”
Section: Ht and The Antineoplastic Drug Resistancementioning
confidence: 99%
“…In preclinical trials the Cisplatin was shown to be effective [29], so the clinical studies were concentrating on this drug combination. Special case report has shown the feasibility [30] and the median survival gain (from 15 ( = 20) to 25 ( = 32) months) [31].…”
Section: Introductionmentioning
confidence: 99%